A Study On The Potential Of Tin Recovery From Iron Ore Tailing - Johar, Muhammad Faris Zamir (Universiti Sains Malaysia, 2022)
The iron ore tailings sample was obtained from an iron processing plant in Bukit Kachi Mine, Kedah. The goal of this study is to characterise and process the tin in iron ore tailings. The method research has been divided into two parts: characterization and processing. The mode of occurrences, grain size, mineral distribution, and liberation analysis assessment were studied using an optical microscope, polarising microscope, and scanning electron microscope (SEM). X-ray fluorescence (XRF) and X-ray diffraction were used to determine the chemical composition of the sample (XRD). The Tin Fluorescence test was used to confirm the presence of tin in the concentrate using light colour spectrum. For the processing method, an iron ore tailings sample undergone comminution process for mineral liberation before gravity separation using the Mozley table. According to SEM analysis, mineral liberation began to give a liberated sign at a size fraction of (-1mm +0.5mm). According to the particle size distribution analysis, 50% of the samples have a size less than 1.1mm and 30% of the samples have a size greater than 1.1mm. According to the findings, the Mozley table separation can improve tin recovery from 0 percent Sn to 4.05% percent Sn. Tin Fluorescence testing revealed the presence of tin in concentrate samples, where the blue colour flame can clearly observe after the test tube dipped with the tin ion solution. In conclusion, tin minerals had been characterized and Mozley table still not suitable for tin recovery in iron ore tailing as the recovery is very low.